1998
DOI: 10.1136/jnnp.65.4.436
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia and chorea in acquired systemic disorders

Abstract: Dystonia and chorea are uncommon abnormal movements which can be seen in a wide array of disorders. One quarter of dystonias and essentially all choreas are symptomatic or secondary, the underlying cause being an identifiable neurodegenerative disorder, hereditary metabolic defect, or acquired systemic medical disorder. Dystonia and chorea associated with neurodegenerative or heritable metabolic disorders have been reviewed frequently.1 Here we review the underlying pathogenesis of chorea and dystonia in acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 129 publications
3
72
1
1
Order By: Relevance
“…Vasculitis was reported as the main pathogenetic mechanism of basal ganglia ischaemia related to neuroborreliosis. Other proposed mechanisms include vasculopathy due to direct basal ganglia invasion by the organism, neuronal injury by an cytotoxin, antibiodies cross-reactivity with basal ganglia epitopes (Janavs et al 1998). The selective pathophysiology that occurs in HD is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasculitis was reported as the main pathogenetic mechanism of basal ganglia ischaemia related to neuroborreliosis. Other proposed mechanisms include vasculopathy due to direct basal ganglia invasion by the organism, neuronal injury by an cytotoxin, antibiodies cross-reactivity with basal ganglia epitopes (Janavs et al 1998). The selective pathophysiology that occurs in HD is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of 1H-MRS to track spectral changes makes it potentially useful for diagnostics and prognostics or as a tool to monitor the effects of treatment when Janavs et al 1998). Too few cases of movement disorders such as chorea and dystonia were described during the course of neuroborreliosis (Piccolo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a cataleptic response induced by activation of the indirect pathway by haloperidol was canceled by excessive activation of the direct pathway by a D 1 receptor agonist SKF82958 in rats . Moreover, several reports have suggested that excessive activation of the direct pathway MSNs is involved in the production of dystonia, one of the major clinical features of HD (Janavs and Aminoff, 1998;Louis et al, 1999;Burbaud, 2012). It is not known whether the indirect pathway MSN-biased activation pattern by TAK-063 would translate to therapeutic benefit in humans.…”
Section: Tablementioning
confidence: 99%
“…1,2 Hemidystonia is almost always secondary to a structural lesion localized in the striatal, pallidal, thalamic, or subthalamic areas. [3][4][5] Unilateral dystonic symptoms may also occur in the course of neurodegenerative diseases such as corticobasal degeneration, progressive supranuclear palsy, or other parkinsonian syndromes.…”
mentioning
confidence: 99%